A Research Tool for Analysing and Monitoring the Extent to which Environmental Issues are Integrated into Teachers' Lessons - Yvonne Nsubuga (Environmental Association of Southern Africa, 2011)
South Africa enjoys strong policy support for the integration of environmental issues into school curricula. However, much doubt exists over the extent to which this has been converted into appropriate classroom practice at the majority of under-resourced rural schools in the country. This article reports on a study which piloted a research tool which can be used to analyse teachers' lessons, with the aim of gaining insight into the extent to which they integrate natural resource management issues. The research tool was based on Bernstein's concept of classification and consisted of five indicators of natural resource management integration into Life Sciences lessons. The study contributes to the design of research tools that can be used to analyse and monitor the integration of environmental issues into teachers' lessons. It also provides some insight into the environmental content of a sample of Grade 10 Life Sciences lessons at four rural underresourced schools in the Eastern Cape.